THE QUALITY OF DATA AND METADATA IN A DATAWAREHOUSE - Carmen Răduţ (Strategii Manageriale)
The data quality is an important concept for the economic applications used in the process of analysis. The databases were revolutionized when they first started being used with large amountsof data. From this point on, an important process is represented by storing multidimensional data in datawarehouses, in order to be processed and analyzed with the purpose of obtaining information which can be used for decision making in various activities. Specialty studies show that most data is not useful for the purpose it has been collected because of both the lack of quality and incorrect techniques of manipulating this data. This study will try to offer a process of obtaining quality data in data archives and how to avoid quality anomalies inside metadata.